2023
DOI: 10.3389/fimmu.2023.1169601
|View full text |Cite
|
Sign up to set email alerts
|

The role of regulatory T cells and follicular T helper cells in HBV infection

Abstract: Hepatitis B has become one of the major global health threats, especially in developing countries and regions. Hepatitis B virus infection greatly increases the risk for liver diseases such as cirrhosis and cancer. However, treatment for hepatitis B is limited when considering the huge base of infected people. The immune response against hepatitis B is mediated mainly by CD8+ T cells, which are key to fighting invading viruses, while regulatory T cells prevent overreaction of the immune response process. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 176 publications
0
3
0
Order By: Relevance
“…[ 91 , 92 ]. Several studies have shown that during chronic HBV infection, Treg cells proliferate dramatically and suppress the anti-HBV immune response [ 93 , 94 ].…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%
“…[ 91 , 92 ]. Several studies have shown that during chronic HBV infection, Treg cells proliferate dramatically and suppress the anti-HBV immune response [ 93 , 94 ].…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%
“…FOXP3 can also form different complexes with different transcription factors, thereby affecting the specificity of Treg cell suppression function. In the IM, FOXP3 in Treg cells can combine with T-bet, a key transcription factor in Th1 cells, due to external environmental stimuli, specifically enhancing the immunosuppressive function of Tregs, which in turn promotes tumor progression (46)(47)(48).…”
Section: Mechanism Of Treg Reprogramming Under Inflammatory Microenvi...mentioning
confidence: 99%
“…This immune 'exhaustion' is characterized by poor cytotoxic T-cell activity and impaired cytokine production [35]. The role of regulatory T cells (Tregs) in this 'immune exhaustion' has been widely demonstrated [36][37][38][39]. In a poorly understood mechanism, HBV infection induces Treg responses [40].…”
Section: Immune Response To Hbvmentioning
confidence: 99%